Probiotics or synbiotics addition to sows’ diets alters colonic microbiome composition and metabolome profiles of offspring pigs - Zhu, Qian; Song, Mingtong; Azad, Md. Abul Kalam; Cheng, Yating; Liu, Yating; Liu, Yang; Blachier, François; Yin, Yulong; Kong, Xiangfeng (Frontiers in Microbiology, 2022)
Little information exists about the effects of maternal probiotics and synbiotics addition on the gut microbiome and metabolome of offspring. The present study evaluated the effects of probiotics or synbiotics addition to sows’ diets on colonic microbiota and their metabolites in offspring using 16S rRNA gene sequencing and metabolome strategy. A total of 64 pregnant Bama mini-pigs were randomly divided into control, antibiotic, probiotics, and synbiotics groups and fed the corresponding experimental diets during pregnancy and lactation. After weaning, two piglets per litter and eight piglets per group were selected and fed a basal diet. The β-diversity analysis showed that the colonic microbiota of offspring had a clear distinction among the four groups at 65 days of age. Maternal probiotics addition increased the Actinobacteria abundance at 65 days of age and Tenericutes and Firmicutes abundances at 95 days of age of offspring compared with the other three groups, whereas maternal antibiotic addition increased Spirochaetes and Proteobacteria abundances at 95 days of age of offspring compared with the other three groups. Metabolomic analysis showed that colonic metabolites were different between the groups, regardless of the days of age. Furthermore, both PICRUSt2 and enrichment analysis of metabolic pathways showed that maternal probiotics and synbiotics addition affected metabolism of carbohydrate, amino acid, cofactors and vitamins in the colonic microbiota. Compared with the control group, the colonic concentration of indole decreased and skatole increased in the probiotics group, whereas indole increased and skatole decreased in the synbiotics group. Maternal probiotics addition increased the colonic concentrations of acetate and butyrate at 65 and 125 days of age, whereas probiotics and synbiotics addition decreased short-chain fatty acids concentrations at 95 days of age. In addition, the colonic concentrations of putrescine, cadaverine, 1,7-heptanediamine, and spermidine were increased in the antibiotic, probiotics, and synbiotics groups compared with the control group at 95 days of age. The correlation analysis showed that Gemmiger, Roseburia, and Faecalibacterium abundances were positively correlated with acetate, propionate, and butyrate concentrations; Gemmiger, Blautia, and Faecalibacterium were positively correlated with putrescine and spermidine; and Faecalibacterium, Blautia, Clostridium, and Streptococcus were positively correlated with (R)-3-hydroxybutyric acid. Collectively, these findings suggest that probiotics and synbiotics addition to sows’ diets exerts effects on offspring pigs by altering gut microbiota composition and their metabolites. The potential beneficial effect on gut health is discussed.